Tobit filtering for nonlinear systems with fading observations under periodic protocol via uniform dynamic encoding–decoding scheme - Yang, Shuo; Hu, Jun; Caballero-Águila, Raquel; Jia, Chaoqing (Communications in nonlinear science & numerical simulation, 2026)
This paper investigates the design and performance evaluation problem of uniform dynamic encoding–decoding-based Tobit filtering algorithm for a class of stochastic time-varying nonlinear systems under the periodic protocol, which are subject to censored measurements and fading observations. The Tobit Type I observation model is exploited to depict the censored measurements and a series of random variables with known statistical properties are introduced to model the fading observations. With the aim of alleviating the network burden, the periodic protocol is applied to regulate the order when the sensor nodes send the measurement data. Moreover, the uniform dynamic encoding–decoding scheme is utilized to strengthen the signal security during transmission. A new Tobit filtering approach with recursive computation advantages is developed such that the optimized upper bound of the filtering error covariance can be obtained at every time step and the explicit expression for the corresponding filter parameter is determined. Additionally, the exponential boundedness of the filtering error is ensured in the mean-square sense by providing a sufficient condition. Finally, the advantages and applications of the presented Tobit filtering strategy are shown by conducting some comparative simulation experiments. •A new nonlinear filtering algorithm is developed to ensure communication security requirement.•A dynamic encoding–decoding scheme during the communication is discussed.•An optimized upper bound regarding filtering error covariance is operated by designing filter gain.•The exponential boundedness performance is conducted by providing rigorous mathematical proof.